2007
DOI: 10.1111/j.1399-6576.2007.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice and routines for day surgery in Sweden: results from a nation‐wide survey

Abstract: In Sweden, a high degree of standardised regime for day surgical practice was found. Post-operative pain is the most common complaint after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 35 publications
0
63
0
1
Order By: Relevance
“…Provision of analgesia after ambulatory surgery remains poor. In two Swedish nationwide surveys of ambulatory surgery, pain was the most common problem at follow-up after discharge in a general (Segerdahl et al, 2008a Level IV) and a paediatric population (Segerdahl et al, 2008b Level IV). Another survey from a single institution found that even at 3 and 4 days after day-stay surgery, 10% and 9% of patients respectively reported moderate to severe pain (Greengrass & Nielsen, 2005 Level IV).…”
Section: Day-stay or Short-stay Surgerymentioning
confidence: 99%
“…Provision of analgesia after ambulatory surgery remains poor. In two Swedish nationwide surveys of ambulatory surgery, pain was the most common problem at follow-up after discharge in a general (Segerdahl et al, 2008a Level IV) and a paediatric population (Segerdahl et al, 2008b Level IV). Another survey from a single institution found that even at 3 and 4 days after day-stay surgery, 10% and 9% of patients respectively reported moderate to severe pain (Greengrass & Nielsen, 2005 Level IV).…”
Section: Day-stay or Short-stay Surgerymentioning
confidence: 99%
“…After that time, with the development of newer and safer anesthetic techniques, and with the modern intravenous anaesthetic agents like propofol, midazolam, and fentanyl, thyroidectomy was performed exclusively under general anaesthesia and in inpatient settings. The current trend now favors minimally invasive thyroid surgery techniques, ambulatory approach, shortening of hospital stay and once more utilizes preferably Local anaesthesia + Monitored Anaesthesia Care (LA + MAC) (1)(2)(3)(4)(5)(6). However, the complexity of the procedure may vary from excision of a single nodule to removal of the entire thyroid gland with lymph dissection to treat cancer, or extirpation of a retrosternal goitre to relieve tracheal compression.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgeries have been transferred from in-hospital to day surgical procedures (e.g. laparoscopic cholecystectomy, anterior cruciate ligament repair, hernia repair in the elderly, shoulder surgery as well as minor procedures for gynaecological prolapse and urine incontinency) (Segerdahl et al, 2007). Day surgery implies admittance, surgery and discharge without an overnight stay (Toftgaard and Parmentier, 2006), and minimal disruption of ordinary life (Mottram, 2010).…”
Section: Introductionmentioning
confidence: 99%